Farmer-centric Scaling of Agroecology Innovations Boosts Crop Productivity and Increases Adoption in Central Tanzania - Desta, Gizaw; Ngowi, Peter (International Crops Research Institute for the Semi-Arid Tropics, 2024)
The ResComm project, "Enabling a Resilient and Prosperous Community through Participatory Agroecological Practices in Central Tanzania," has significantly enhanced agricultural productivity and resilience among smallholder farmers. Using a lead farmer-centric approach across eight community learning sites, the project promoted integrated agroecological practices, including improved crop varieties, intercropping, tie ridges, and Fanya juu/ chini* soil conservation techniques. Between 2021 and 2023, over 650 farmers directly adopted these innovations, benefiting over 7,300 indirectly, with an additional 400 adopting them in 2024. Yields of pigeonpea and sorghum increased by up to 2–3 times, and adoption rates in participating villages reached 60–90%. The project also empowered women, who made up 45% of beneficiaries, and delivered environmental and economic benefits, including increased income and reduced land degradation. ResComm demonstrates the potential for scaling sustainable practices across similar regions, fostering agricultural transformation, improved livelihoods, and climate resilience.